2020
DOI: 10.3390/ijerph17134896
|View full text |Cite
|
Sign up to set email alerts
|

Communication Skills, Problem-Solving Ability, Understanding of Patients’ Conditions, and Nurse’s Perception of Professionalism among Clinical Nurses: A Structural Equation Model Analysis

Abstract: This study was intended to confirm the structural relationship between clinical nurse communication skills, problem-solving ability, understanding of patients’ conditions, and nurse’s perception of professionalism. Due to changes in the healthcare environment, it is becoming difficult to meet the needs of patients, and it is becoming very important to improve the ability to perform professional nursing jobs to meet expectations. In this study method, structural model analysis was applied to identify fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
0
16
2
Order By: Relevance
“…The educational needs of proficiency and collaboration were also high in this study. One explanation is that proficiency and collaboration are required to cope with crisis appropriately, reduce medical error, and ensure patient safety [ 4 , 31 , 32 , 33 ]. Furthermore, the high educational needs for leadership, professional development, collaboration, and empathy in this study suggest the necessity of education for technical and non-technical competencies in OR competency.…”
Section: Discussionmentioning
confidence: 99%
“…The educational needs of proficiency and collaboration were also high in this study. One explanation is that proficiency and collaboration are required to cope with crisis appropriately, reduce medical error, and ensure patient safety [ 4 , 31 , 32 , 33 ]. Furthermore, the high educational needs for leadership, professional development, collaboration, and empathy in this study suggest the necessity of education for technical and non-technical competencies in OR competency.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that as age and professional experience of nurses' increase, their critical thinking, problem-solving, decisionmaking, and communication skills also increase. 41,46,47 This shows the importance of experience in learning and applying therapeutic communication techniques. Self-disclosure is also a therapeutic communication process for nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Level 5 (9-10) Fully covers the target knowledge; finds the solution to the task Level 4 (7-8) Covers the majority of the target knowledge; finds the task solution, but some details are inaccurate Level 3 (5)(6) Covers some of the target knowledge; presents the task solution with noticeable errors Level 2 (3)(4) Covers only a limited range of the target knowledge; fails to find the task solution Level 1 (1)(2) Fails to address the task; answer is completely unrelated to the task…”
Section: Level Evaluation Criteriamentioning
confidence: 99%
“…Collaborative problem solving (CPS) has been listed as one of the core competencies in the 21st century [1]. The digital era has witnessed the crucial influence of online CPS on individuals' working performance and well-being [2,3], especially during the post-pandemic recovery. From the perspective of learning science, it has been also demonstrated that CPS can lead to deeper understanding of the topic in computer-supported collaborative learning (CSCL) settings [4].…”
Section: Introductionmentioning
confidence: 99%